Reconfiguring Human, Nonhuman and Posthuman in Literature and Culture - Karkulehto, Sanna; Koistinen, Aino-Kaisa; Varis, Essi (Perspectives on the Non-Human in Literature and Culture, 2020)
The time has come for human cultures to seriously think, to severely conceptualize, and to earnestly fabulate about all the nonhuman critters we share our world with, and to consider how to strive for more ethical cohabitation. Reconfiguring Human, Nonhuman and Posthuman in Literature and Culture tackles this severe matter within the framework of literary and cultural studies. The emphasis of the inquiry is on the various ways actual and fictional nonhumans are reconfigured in contemporary culture - although, as long as the domain of nonhumanity is carved in the negative space of humanity, addressing these issues will inevitably clamor for the reconfiguration of the human as well.